Effect Of Ciprofloxacin And Resveratrol Combination On Expression of pelA , pslD, mexA Genes of Pseudomonas aeruginosa isolates from lower respiratory tracts. - Sattar, Samaa Salman; Kareem Ibrahim Mubarak (ASJ - Academic Science Journal, 2025)
A total of  200  sputum specimens  were collected from the patients infection with  Lower Respiratory Tract ( LRT) who attended  Baquba Teaching Hospital and Chest Diseases Center Baquab city /Iraq. The study aimed to investigate the effect of resveratrol  as efflux pumps inhibitor on ciprofloxacin MIC and compare the effect of two agents on expression of pelA , pslD, mexA genes for P. aeruginosa isolates ,all specimens were inoculated on suitable media for isolation and identification of bacteria by morphological ,  biochemical tests and  molecular diagnosis using the polymerase chain reaction .The results showed that overall prevalence of P. aeruginosa among patients was 24  (12%)   isolates  were identified .The percentages  of the phenotypic detection  haemolysin  test ,  pyocinin pigment    100 %  and 95.83%   respectively. Our study reveal that sub-MIC of  Resveratrol cause reduction in MIC of Ciprofloxacin for most isolates,  . The combination effect of  of resveratrol and Ciprofloxacin  on the expression of  Biofilms formation genes pelA, psID and efflux pump gene mexA revealed a synergistic impact were cause a reduction in mean of gene expression of this  three  genes ( 0.45  , 0. 60 . 0.90 )  respectively  in  three MDR P. aeruginosa isolates.